Longitudinal Analysis of Fecal Microbiome and Pathologic Processes in a Rotenone Induced Mice Model of Parkinson’s Disease - Yang, Xiaodong; Qian, Yiwei; Xu, Shaoqing; Song, Yanyan; Xiao, Qin (Frontiers in Aging Neuroscience, 2018)
Recent studies reported an association between gut microbiota composition and Parkinson’s disease (PD). However, we know little about the relationship between microbiome dysbiosis and the pathogenesis of PD. The objective of this study was to describe the evolution of fecal microbiota using an oral rotenone model of PD from a longitudinal study over a period of 4 weeks. Gastrointestinal function was assessed by measuring fecal pellet output, motor functions was assessed by open-field and pole tests every week. α-synuclein pathology, inflammation and tyrosine hydroxylase (TH) neuron loss from the middle brain were also analyzed. Fecal samples were collected every week followed by 16S rRNA sequencing and bioinformatics analysis. We reported that chronically oral administered rotenone caused gastrointestinal dysfunction and microbiome dysbiosis prior to motor dysfunction and central nervous system (CNS) pathology. 16S rRNA sequencing of fecal microbiome showed rotenone-treated mice exhibited fecal microbiota dysbiosis characterized by an overall decrease in bacterial diversity and a significant change of microbiota composition, notably members of the phyla Firmicutes and Bacteroidetes, with an increase in Firmicutes/Bacteroidetes ratio after 3 weeks of rotenone treatment. Moreover, rotenone-induced gastrointestinal and motor dysfunctions were observed to be robustly correlated with changes in the composition of fecal microbiota. Our results demonstrated that gut microbiome perturbation might contribute to rotenone toxicity in the initiation of PD and brought a new insight in the pathogenesis of PD. Novel therapeutic options aimed at modifying the gut microbiota composition might postpone the onset and following cascade of neurodegeneration.